METHODS OF DEVELOPING STUDENTS' CRITICAL THINKING USING PROBLEM TEACHING METHODS IN MOTHER LANGUAGE CLASSES - Kholdarova Iroda Valijonovna; Abdumutalova Mukhayokhan Kahramonjon qizi (Western European Studies, 2024)
This article provides information on ways to develop students' critical thinking using problem-based learning methods in mother tongue classes.
Keywords: Critical thinking; ability; speech